2014
DOI: 10.3324/haematol.2013.084640
|View full text |Cite
|
Sign up to set email alerts
|

Three major uncertainties in the antibody therapy of cancer

Abstract: Antibodies against surface molecules of human tumors are now frequently administered in combination with strong chemotherapy, increasing therapeutic efficacy but making the task of elucidating immunological events more difficult. Experiments on genetically manipulated mice indicate that antibody efficacy is greatest when IgG antibody coating tumor cells is engaged by the Fcγ-receptors of effector cells, chiefly the monocyte/macrophage lineage. Evidence suggests lesser roles for NK cells, neutrophils, receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…Tumor cells are populations with high heterogeneity. Trogocytic exchanges of membrane patches containing cell‐surface proteins between surrounding tumor cells in vivo are relevant to the phenotypic and functional properties of the host cells . A study by LeMaoult et al .…”
Section: Trogocytosis Of Hla‐g From Tumor Cells To Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells are populations with high heterogeneity. Trogocytic exchanges of membrane patches containing cell‐surface proteins between surrounding tumor cells in vivo are relevant to the phenotypic and functional properties of the host cells . A study by LeMaoult et al .…”
Section: Trogocytosis Of Hla‐g From Tumor Cells To Tumor Cellsmentioning
confidence: 99%
“…Trogocytic exchanges of membrane patches containing cell-surface proteins between surrounding tumor cells in vivo are relevant to the phenotypic and functional properties of the host cells. 43 A study by LeMaoult et al 30 demonstrated that haematological tumor cell lines can uptake HLA-G molecules from either allogeneic or autologous donors. In that study, the trogocytic capability of tumor cells from haematological malignancy patients ex vivo and in ten haematological tumor cell lines in vitro was investigated.…”
Section: Trogocytosis Of Hla-g From Tumor Cells To Tumor Cellsmentioning
confidence: 99%
“…The FcgRs bind mAb-coated tissues through the IgG crystallizable fragment (Fc) and kill the target by phagocytosis or cell-mediated cytotoxic processes. 2 Human cells express 5 activating FcgRs (CD64, the "high affinity" FcgR, and the "low affinity" FcgRs CD32A, CD32C, CD16A, CD16B) and one "low affinity" inhibitory receptor (CD32B) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These include variables such as cell line genetic drift (Hughes et al, 2007; Kleensang et al, 2016), circadian biological responses to therapy (Fu and Kettner, 2013), mouse strain stocks (Clayton and Collins, 2014), housing temperature in mouse facilities (Kokolus et al, 2013), and the obesity and microbiome of recipient mice (Klevorn and Teague, 2016; Macpherson and McCoy, 2015). Additionally, a differential response to immunotherapy can occur due to heterogeneity in individual tumor microenvironments (Grosso and Jure-Kunkel, 2013), which has also been observed in the clinical setting (Ascierto and Marincola, 2014; Stevenson, 2014). Whether these or other factors influence the outcomes of this study is open to hypothesizing and further investigation, which is facilitated by direct replications and transparent reporting.…”
Section: Resultsmentioning
confidence: 99%